2021
DOI: 10.3390/ijms22031285
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical Effects of 4-(2Chloro-4-Fluorobenzyl)-3-(2-Thienyl)-1,2,4-Oxadiazol-5(4H)-One in the Pentylenetetrazole (PTZ)-Induced Epileptic Seizure Zebrafish Model

Abstract: Epilepsy is one of the most common neurological disorders, and it is characterized by spontaneous seizures. In a previous study, we identified 4-(2-chloro-4-fluorobenzyl)-3-(2-thienyl)-1,2,4-oxadiazol-5(4H)-one (GM-90432) as a novel anti-epileptic agent in chemically- or genetically-induced epileptic zebrafish and mouse models. In this study, we investigated the anti-epileptic effects of GM-90432 through neurochemical profiling-based approach to understand the neuroprotective mechanism in a pentylenetetrazole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…The PTZ-induced model of tonic-clonic seizures in zebrafish is commonly used for initial screening of potential natural and synthetic anticonvulsant agents. , Larval zebrafish, when incubated in PTZ solution, experience seizures that behaviorally manifested as a hyperactivity. , Recently, however, it was revealed that relying on the locomotor changes when assessing antiseizure activity of compounds may give false positive results . Therefore, final confirmation should be done using electroencephalographic (EEG) assay.…”
Section: Resultsmentioning
confidence: 99%
“…The PTZ-induced model of tonic-clonic seizures in zebrafish is commonly used for initial screening of potential natural and synthetic anticonvulsant agents. , Larval zebrafish, when incubated in PTZ solution, experience seizures that behaviorally manifested as a hyperactivity. , Recently, however, it was revealed that relying on the locomotor changes when assessing antiseizure activity of compounds may give false positive results . Therefore, final confirmation should be done using electroencephalographic (EEG) assay.…”
Section: Resultsmentioning
confidence: 99%
“…To explore whether these altered activities were provoked by changes in neurotransmitter levels, we measured the levels of various neurotransmitters in wild-type and knockout brains [32]. However, we observed no signi cant changes in neurotransmitters, such as glutamate, GABA, dopamine, serotonin, histamine, and norepinephrine, in either wild-type or knockout brains (Fig.…”
Section: Broad Expression Of Fam19a5a In the Zebra Sh Brainmentioning
confidence: 87%
“…To assess neurotransmitter levels in the adult brain, we performed a protocol identical to that previously described [32]. Each fam19a5a-wild-type and fam19a5a-knockout brain (n = 12) was added to nine volumes (w/v) of pre-chilled distilled water and homogenized on ice using a probe sonicator (Ultrasonic processor VCX-130, Sonics & Materials Inc., Newtown, CT, USA).…”
Section: Quantitative Measurement Of Neurotransmitters In the Zebra S...mentioning
confidence: 99%
“…The zebrafish (Danio rerio) is a promising vertebrate for the screening of the central nervous system (CNS) with a high degree of genetic compatibility, and it also displays comprehensive neurochemistry similar to human beings [14,15]. The zebrafish's organ formation and pharmacokinetic system are very similar to those of humans [16,17].…”
Section: Introductionmentioning
confidence: 99%